2021
DOI: 10.1002/jmv.27415
|View full text |Cite
|
Sign up to set email alerts
|

The COVID‐19 Yorkshire Rehabilitation Scale (C19‐YRS): Application and psychometric analysis in a post‐COVID‐19 syndrome cohort

Abstract: As our understanding of the nature and prevalence of post-coronavirus disease 2019 (COVID-19) syndrome (PCS) is increasing, a measure of the impact of COVID-19 could provide valuable insights into patients' perceptions in clinical trials and epidemiological studies as well as routine clinical practice. To evaluate the clinical usefulness and psychometric properties of the COVID-19 Yorkshire Rehabilitation Scale (C19-YRS) in patients with PCS, a prospective, observational study of 187 consecutive patients atten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 21 publications
(44 reference statements)
2
69
0
1
Order By: Relevance
“… 5 26 Existing symptom measures (n=6) with good face validity in the context of long covid were reviewed to establish whether a new instrument for symptom burden that measured patient reported outcomes was needed. 20 27 28 29 30 31 When mapped to the conceptual framework, symptom coverage of these instruments ranged from 27.0% to 60.3%: mean 34.5% (standard deviation 16.2%). Supplementary table S1 presents the concept coverage matrix mapping symptom coverage of the candidate instruments to the conceptual framework.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 26 Existing symptom measures (n=6) with good face validity in the context of long covid were reviewed to establish whether a new instrument for symptom burden that measured patient reported outcomes was needed. 20 27 28 29 30 31 When mapped to the conceptual framework, symptom coverage of these instruments ranged from 27.0% to 60.3%: mean 34.5% (standard deviation 16.2%). Supplementary table S1 presents the concept coverage matrix mapping symptom coverage of the candidate instruments to the conceptual framework.…”
Section: Methodsmentioning
confidence: 99%
“… 16 17 18 Validated instruments to measure patient reported outcomes have recently been developed to measure the global impact of long covid, and several unvalidated screening tools, surveys, and questionnaires are also available. 19 20 However, individuals living with long covid have suggested that existing self-report measures fail to capture the breadth of experienced symptoms. 10 21 22 To address the need for a comprehensive measure of self-reported symptom burden specific to long covid, we used Rasch analysis to develop and validate, in accordance with US Food and Drug Administration guidance, a novel instrument measuring patient reported outcomes, the symptom burden questionnaire for long covid (SBQ-LC).…”
Section: Introductionmentioning
confidence: 99%
“…For example, O'Connor and coworkers used accepted psychometric measures to characterize the COVID‐19 Yorkshire Rehabilitation Scale. 8 The apparent types and severity of post‐COVID‐19 symptoms might differ based on the instruments used. That used in the present study is available online (Supporting Information Data ).…”
Section: Discussionmentioning
confidence: 99%
“…The C19-YRS possesses internal consistency, content validity and clinical usefulness for use with persons with Long COVID. 67 …”
Section: Methods and Analysismentioning
confidence: 99%